Improvement of reflection-mode pulse oximetry for measurement of SpO2 in newborns - Stockwell, Simon John (2024)
Measurement of the photoplethysmogram in the immediate moments after birth is a historically challenging setting to obtain rapid and accurate data in these critical early minutes. Motion artefacts, low perfusion and noisy signals all contribute to an inability to measure the photoplethysmogram to derive the necessary vital signs to show improvement in the condition of the newborn. Previous clinical trials from 2017 on infants born by elective caesarean section showed an ability to accurately and rapidly track the R ratio of an infant (via the forehead) with a strong correlation (0.98) when compared against a commercial pulse oximeter in the delivery room. A novel algorithm for calculation of the perfusion index is presented.